Modular Synthesis of α-Substituted Alkenyl Acetals by a Palladium-Catalyzed Suzuki Reaction of α-Haloalkenyl Acetals with Organoboranes - Zhang, Li (Synlett, 2021)
A modular and straightforward synthetic strategy for the preparation of α-substituted alkenyl acetals has been developed. α-Haloalkenyl acetals react smoothly with (het)aryl boronic acids, aryl boronates, or B-alkyl-9-borabicyclo[3.3.1]nonanes through Pd-catalyzed Suzuki cross-coupling under mild conditions with good to high yields. This protocol features a broad substrate scope and good functional-group compatibility, and is easily scaled up.
Keywords: alkenyl acetals; palladium catalysis; Suzuki reaction; cross-coupling; arylboronic acids; arylation